Towards equality for women : progress in legislation since the adoption of the Convention on the Elimination of All Forms of Discrimination against Women - Binstock, Hanna (UN SantiagoCL, 1998)
Emphasizes the progress that has been made in the region with regard to the adoption of legislation aimed at ensuring the integration of women into economic and social development and proposes guidelines for further action. Reviews different international and regional instruments that serve as a framework for action. Analyzes the progress that has been achieved in regard to legislation, based on a broad definition of discrimination and a comprehensive approach to the legal system.